Post-vasectomy depression: a case report and literature review - Subahani Shaik; Ravi Philip Rajkumar (Mental Illness)
Vasectomy is a commonly performed and relatively safe procedure, with low reported rates of psychological morbidity, though there is some variability across studies. Depression following a vasectomy is relatively infrequent. A married man aged 30 developed a chronic depressive episode, lasting four years and resistant to an adequate trial of fluoxetine, following a vasectomy. His depression was heralded by a post-operative panic attack, and was accompanied by medically unexplained symptoms and the attribution of all his symptoms to the procedure – a belief that was shared by his family. Psychological complications of vasectomy have generally been studied under four heads: sexual dysfunction, effects on marital relationships, chronic post-operative pain, and other complications including anxiety and depression. These complications have generally been reported at higher rates in developing countries, and are linked to poor knowledge about the procedure and inadequate pre-operative counseling. The implications of the existing literature for the patient’s current complaints, and the mechanisms and risk factors involved, are discussed in the light of existing research. Suggestions for the prevention and treatment of post-vasectomy depression are also outlined.